From New Molecular Insights to New Treatment Options in Endometrial Cancer - Ursula Hasler-Strub (healthbook TIMES. Oncology Hematology)
Endometrial cancer remains the most common gynecological cancer in Europe and the US, with excellent survival rates in patients with early-stage disease.^1^ However, the prognosis of advanced/metastatic endometrial cancer is dismal. There is a considerable need to refine treatment options in the adjuvant and metastatic settings, especially after the failure of first-line platinum-based chemotherapy. Nowadays, immune checkpoint inhibitors (ICIs) have the potential to change the systemic treatment landscape of endometrial cancer.